The Phenomenon Of Impulse Buying Of Generation Z Consumers In An Interactive Social Media-Based Trading Environment - Surya Budiman (Implikasi: Jurnal Manajemen Sumber Daya Manusia, 2026)
This study aims to explore in-depth the phenomenon of impulsive buying among Generation Z consumers in an interactive social media-based commerce environment (social commerce). The rapid development of interactive features such as live streaming, personalized algorithmic recommendations, and the integration of instant transactions has significantly changed the shopping behavior patterns of the younger generation. Using a qualitative approach with a phenomenological method, data were collected through in-depth interviews with 12 Generation Z informants who actively transact on social media platforms, and reinforced by digital observation. The results show that the urge to impulsive buy is triggered by a combination of technological stimulation and subjective emotional dynamics. Real-time interactive features trigger the Fear of Missing Out (FOMO) phenomenon and create a sense of emotional attachment between viewers and presenters. Furthermore, the ease of navigating digital payments minimizes rational barriers to decision-making. This spontaneous experience is often followed by immediate emotional gratification, although some informants also experience post-purchase regret. The implications of this study confirm that Generation Z's impulsive behavior on social media is not simply a response to discounted prices, but rather the result of constructing a highly interactive and immersive shopping experience. These findings provide practical contributions for business actors in designing ethical and persuasive digital marketing strategies, as well as serving as an academic reference regarding digital consumer psychology.